Perempuan dalam Novel â€œBidadari Bermata Beningâ€ Karya Habiburrahman El Shirazy - Anita Anita; Zainal Rafli; Siti Ansoriyah (Jurusan Tadris Bahasa Indonesia, 2020)
Women are considered weak and are considered inferior to men. This is widely used in novels as a form of literary work that can provide changes in thinking. The purpose of this research is to examine the value of women